Study on the improved electromechanical properties of composited dielectric elastomer by tailoring three-dimensional segregated multi-walled carbon nanotube (MWCNT) network. (26th May 2022) - Huang, Yanhao; Xu, Zewang; Shi, Xiaohui; Zheng, Shaodi; Wu, Xiaotian; Liu, Zhengying; Bao, Ruiying; Yang, Wei; Yang, Mingbo
Abstract: High permittivity and large actuation strain under low actuation voltage have been the "hotspot" on the development and application of dielectric elastomer actuators (DEAs) for decades. In this work, by coating multi-walled carbon nanotube (MWCNT)/silicon rubber (SR) composite on the surface of nickel foam, after which the nickel foam was etched, the segregated MWCNT network structure was filled and encapsulated by SR. As a result, an isolated three-dimensional (3D) MWCNT network was successfully introduced into the SR elastomer matrix. Studies showed that owing to the large amount of accumulated charge on the large polarization interface between MWCNT and SR, high dielectric constant value as high as 10.39 at 1 kHz under 0.8 wt % MWCNT can be endowed to the composited elastomer. In addition, because discontinuity of adjacent MWCNTs in the 3D MWCNT network, the dielectric loss and elastic modulus of the composited elastomer has been significantly lowered, providing a high actuated strain of about 11.61% at a low electric field of 10.1 V·μm −1 under a filler content of 0.6 wt % to the composites. This finding raises a long-range prospect to readily and reliably prepare high-performance polymer based dielectric materials, and the 3D-MWCNT/SR composite elastomer seizes a great potential to be applicated as high-performance DEAs. Graphical abstract: Image 1